DETERMINATION OF TANNIN CONTENT AND ANTIBACTERIAL ACTIVITY OF CHROMOLAENA ODORATA L. - Rahmawati; Baits, Muzakkir; Naid, Tadjuddin; Azmi, Nurul; Rumata, Raudhia Wulandari (Universal Journal of Pharmaceutical Research, 2025)
Aims and objectives: To ascertain the antibacterial capability using TLC-bioautography and the tannin content using the UV-Vis spectrophotometric method in the ethanol extract of kopasanda (Chromolaena odorata L.) leaves. Methods: Tannins quantitatively utilizing the UV-Vis spectrophotometric technique using the folin ciocalteu reagent at a wavelength of up to 687 nm. Antibacterial potential against gastrointestinal infection-causing bacteria (Salmonella typhi, Vibrio cholerae, Escherichia coli, and Shigella dysentriae) is assessed using TLC-bioautography technique. Results: The tannin content of the ethanol extract of kopasanda leaves (Chromolaena odorata L.) is 41.9064±0.26 mgTAE/g extract. Escherichia coli, Shigella dysentriae, Salmonella typhi, and Vibrio cholerae, respectively, create inhibitory zones in the antibacterial potential test that yields 7, 8, 8, and 7 stains. Tannins, flavonoids, alkaloids, and saponins are believed to be among the chemicals found in the TLC results obtained with stain spraying reagents 1, 3, 5, and 4, respectively. Conclusions: The average tannin concentration of the ethanol extract of kopasanda leaves (Chromolaena odorata L.) is 41.9064±0.26 mgTAE/g extract, and it has antibacterial properties against germs that cause gastrointestinal illnesses. Peer Review History: Received 22 September 2024; Reviewed 3 November; Accepted 15 December; Available online 15 January 2025 Academic Editor: Dr. Amany Mohamed Alboghdadly , Ibn Sina National College for Medical Studies in Jeddah, Saudi Arabia, amanyalboghdadly@gmail.com Reviewers: Dr. Robert Tungadi, State University of Gorontalo, Indonesia, rtungadi@yahoo.com Dr. Rawaa Souhil Al-Kayali, Aleppo University, Syria, rawah67@hotmail.com